Satisfacción laboral y motivación en aprendices de una empresa sector avícola colombiano (2020)
In this article an investigation was carried out with apprentices of the administrative area from a company in the Colombian poultry sector, implemented in QSJ (job satisfaction questionnaire) under a descriptive quantitative approach, with a sample of 10 people chosen at random from the administrative headquartersin order to know satisfaction, motivation, identification, recognition, safe conditions and perception regarding their practice and to establish how satisfied they are at work in their practical stages